Digital filters basics and design - Schlichthärle, Dietrich 1949-; SpringerLink (Online service). (Heidelberg New York Springer-Verlag, 2011)
The second, substantially enlarged edition of the textbook gives a comprehensive insight into the characteristics and the design of digital filters. It briefly introduces the theory of continuous-time systems and the design methods for analog filters. Discrete-time systems, the basic structures of digital filters, sampling theorem, and the design of IIR filters are widely discussed. The author devotes important parts to the design of non-recursive filters and the effects of finite register length. The explanation of techniques like oversampling and noise shaping concludes the book.
Continuous-Time Systems -- Analog Filters -- Discrete-Time Systems -- Sampling Theorem -- Filter Structures -- Design of IIR Filters -- Design of FIR Filters -- Effects of Finite Register Length -- Oversampling and Noise Shaping -- Appendix -- Index.
Electronic reproduction.
Keywords: Signal processing -- Mathematics; Digital filters (Mathematics); Electronic books